First International Conference of Confederations of Epidemiological Associations (ICRMSW 2013) - Banerjee, Indrajit (Nepal Journal of Epidemiology, 2013)
It gives me immense pleasure to witness and participate in the International Conference of research Methodology and Scientific Writing (ICRMSW-2013) organized by Mahatma Gandhi University and Confederation of Epidemiological Associations. It was the 1st Conference Confederation of Epidemiological Associations (CEA) being held at Kottayam, Kerala from December 20-22nd 2013. DOI: http://dx.doi.org/10.3126/nje.v3i4.9521